DIPG-15. Major tumor regressions in H3K27M-mutated diffuse midline glioma (DMG) following sequential intravenous (IV) and intracerebroventricular (ICV) delivery of GD2-CAR T-cells. (3rd June 2022) - Monje, Michelle; Majzner, Robbie; Mahdi, Jasia; Ramakrishna, Sneha; Patel, Shabnum; Chinnasamy, Harshini; Yeom, Kristen; Schultz, Liora; Barsan, Valentin; Richards, Rebecca; Campen, Cynthia; Reschke, Agnes; et al.
Abstract: BACKGROUND: H3K27M-mutated DMGs express high levels of the disialoganglioside GD2 and GD2-CAR T-cells (GD2-CART) regress DMG in preclinical models. METHODS: NCT04196413 is a 3 + 3 Phase I dose escalation trial testing GD2-CART in patients with biopsy-proved H3K27M DMG, with dose-limiting toxicities (DLT) considered independently for DIPG and spinal DMG (sDMG). Arm A tested escalating doses of IV GD2-CART (DL1=1e6 GD2-CART/kg; DL2=3e6 GD2-CART/kg) following lymphodepletion (LD). After the DLT period, patients with clinical and/or radiographic benefit were eligible for subsequent ICV GD2-CART infusions (10-30e6 GD2-CART) administered via Ommaya without LD. RESULTS: Twelve subjects were treated after standard radiotherapy, 7 of whom began treatment at the time of progression [n=4 DL1 (3 DIPG/1 sDMG); n=8 DL2 (6 DIPG/2 sDMG)]. No DLTs were observed on DL1. Three subjects experienced DLT on DL2 (2 DIPG/1 sDMG) due to grade-4 cytokine release syndrome (CRS). On both dose levels, all subjects exhibited transient symptoms related to on-tumor inflammation, termed Tumor Inflammation-Associated Neurotoxicity (TIAN); no DLT due to TIAN has occurred. Ten subjects experienced radiographic and/or clinical benefit after IV infusion and received subsequent ICV infusions (median=4 ICV infusions/pt, range=1-7). ICV infusions were not associated with high-grade CRS. Four patients continue to receive ICV infusions on study and have experienced continued clinical and radiographic benefit, currently 7-11 months following enrollment. Two patients (one sDMG, one DIPG) have experienced near-complete (>95%) tumor volume reduction. CONCLUSIONS: IV treatment of DIPG and sDMG with GD2-CART is safe at a dose of 1e6/kg, but associated with frequent high-grade CRS at 3e6/kg. ICV GD2-CART has been well tolerated and has mediated impressive sustained clinical benefit in some patients with DIPG/sDMG. Given these findings, we are launching a new arm to assess safety and activity and to define the recommended phase 2 dose for ICV delivery of GD2-CART without LD.